Development of an Acid–Base Module Based on Problem-Based Learning Integrated with TPACK to Improve Senior High School Students’ Learning Outcomes - Rela Faradina; Desy Kurniawati; Budhi Oktavia; Alizar (Jurnal Penelitian Pendidikan IPA, 2025)
The Merdeka Curriculum emphasizes students’ ability to understand and apply their conceptual knowledge to solve contextual problems. This study aims to determine the validity, practicality, and effectiveness of an acid–base module based on problem-based learning integrated with TPACK in improving the learning outcomes of Phase F senior high school (SMA/MA) students. The development model used in this research was the 4-D model. The acid–base module was validated by three chemistry lecturers and two chemistry teachers. The practicality test of the module was conducted by three chemistry teachers and 31 students. The effectiveness of the module in improving learning outcomes was analyzed using the N-gain test. The validity test was analyzed using Aiken’s V, which consisted of content and construct validity, yielding results of 0.89 and 0.91, respectively, both categorized as valid. The practicality results from teachers and students were 98.61% and 86.87%, respectively, both in the high category. The N-gain analysis resulted in a value of g = 0.79, categorized as high. Based on the hypothesis test, the calculated t-value was greater than the critical t-value. These findings confirm that the developed acid–base module based on problem-based learning integrated with TPACK is valid, practical, and effective for significantly enhancing students’ learning outcomes.